Better Students Ask More Questions.
1 Answer | add yours
You should use the following trigonometric identity for an inverse trigonometric function whose argument is negative, such that:
`arc cos (-a) = pi - arc cos a`
Reasoning by analogy, yields:
`arc cos (-1) = pi - arc cos 1`
Replacing 0 for ` arc cos 1 ` and `pi/2` for `arc sin 1` yields:
`arc cos (-1) + arc sin 1 = pi - 0 + pi/2`
Bringing the terms to the right to a common denominator yields:
`arc cos (-1) + arc sin 1 = (2pi + pi)/2`
`arc cos (-1) + arc sin 1 = (3pi)/2`
Hence, evaluating `arc cos (-1) + arc sin 1` yields `arc cos (-1) + arc sin 1 = (3pi)/2` .
Posted by sciencesolve on July 17, 2013 at 5:28 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.